227 Multiple Outbreak Of SARS-COVID-19 In Surgical Wards at The Tertiary Hospital. (12th October 2021) - Karki, B B; Mohammad, S; Chung, W; Eltweri, A; Sauodi, T; Dennison, A; Garcea, G
Abstract: Background: Since the second surge of SARS-COVID-19 on 18 th of September, additional several measures were introduced, and pathways created in order to execute safe surgical practices and protect both patients and staff from SARS-COVID-19. Despite these measures, there have been reported cases of outbreaks in various parts of UK amongst patients and clinical staff. Method: Three outbreaks in the past 6 weeks (10, September 2020 to 21, October 2020) were reported in our surgical wards and we compiled the timing, initial source, number of affected individuals and immediate management steps taken. Results: Following the first outbreak on wards, 28-day surveillance helped us understand responsible variants. Several staff members were found walking out of hospital, in groups once they had removed their PPEs. Communal lunching with inadequate social distancing, attending work with symptoms (albeit atypical for COVID), sharing cars to/from work or not wearing PPE correctly were highlighted in the subsequent investigations. The reduction in number of affected individuals during the last two incidents reflected a degree of efficacy of the implemented preventative measures, which were reviewed again following the subsequent incidents. Conclusions: In the present climate, a robust and prompt response to outbreaks is required. Continual iteration with regards to the need for PPE, adequate social distancing and avoiding over-crowding in communal areas is paramount to reduce the probability of ward outbreaks and inter-professional transmission. Asymptomatic staff testing, particularly in high-risk areas could also be considered but would require adequate laboratory capacity and rapid turnaround of test results.